Simultaneous effective sludge stabilization and direct electricity generation by merging microbial fuel cell (MFC) and Fered-Fenton reactor: An experimental study. (December 2018) - Rasouli Sadabad, Hamed; Badalians Gholikandi, Gagik
Abstract: Harvesting bioenergy from waste materials has fascinated noticeable attention in recent decades. In this respect, it is expected that the recovery of sustainable energy from sewage sludge will become more and more of interest. Improving the efficiency of currently utilized methods and removing their limitations are the main issues that investigations have been concentrated on them. In this study, a novel package has been designed and experimentally investigated. The main purpose of the current study is attaining an effective system which would be able to effectively stabilize the sewage sludge in considerably low retention times simultaneous with direct electricity generation. Therefore, a two-chamber microbial fuel cell (MFC) and an electrochemical advanced oxidation process (EAOP) reactor (based on Fered-Fenton process) have been merged to each other to reach this goal and the performance of the package has been modeled and optimized by response surface methodology (RSM). Also, the optimal conditions of the package's performance have been determined. The accuracy of the proposed models have been confirmed by various experiments and evaluating the related literature. According to the results, the package demonstrated its best performance when the pHEAOP, IEAOP, the retention time, Tpackage, [Fe 2+ ]/[H2 O2 ], and [H2 O2 ] are 4, 1500 mA/cm 2, 4 h, 35 ᵒC, 0.75 and 1500 mg L −1, respectively. In this condition, the package generated 5700 mW  m−3 as the maximum generated electrical power density and more than 75% as the VSS removal efficiency. Highlights: A MFC and an EAOP reactors have been merged to each other to form a novel package. Effective direct electricity generation and sludge stabilization achieved. The package performance has been modeled by response surface methodology (RSM). The processes optimal conditions determined and also, proved by experiments.